Novel Combination Therapies for the Treatment of Bladder Cancer - Peng, Mei; Xiao, Di; Bu, Yizhi; Long, Jiahui; Yang, Xue; Lv, Shuhe; Yang, Xiaoping (Frontiers in Oncology, 2021)
Bladder cancer is the ninth most frequently diagnosed cancer world-wide and ranks 13th in cancer-related death. Two tremendous breakthroughs in bladder cancer therapy over the last decades are the approval of immune checkpoint inhibitors（ICIs）and the fibroblast growth factor receptor tyrosine kinase inhibitor (FGFR-TKI) erdafitinib for treating this deadly disease. Despite the beneficial effects for these approaches, the low response rate and the potential cancer resistance are major concerns. Hence, novel combination therapies to overcome these limitations have been investigated. In this context, combining immunotherapy with targeted drugs is an appealing therapeutic option to improve response and reduce the emergence of resistance in the management of bladder cancer. In this review, the rationale of using different therapeutic combinations is discussed according to the mechanistic differences, emphasizing the efficacy and safety based on evidence collected from preclinical and clinical studies. Finally, we highlight the limitations of these combinations and provide suggestions for further efforts in this challenging field.